Implementation of Blended Learning through Youtube Media to Improve Students’ Speaking Skill - Cynantia Rachmijati; Anita Anggraeni; Dewi Listia Apriliyanti (OKARA: Jurnal Bahasa dan Sastra, 2019)
With new technology and the way students learn, a vlog is one way to improve students' speaking skills. This research focuses on speaking skill via vlog to improve students' speaking and creativity skills and analyze the interrelationship between the implementation of blended learning and an increase in student self-confidence. This research used mixed methods. The subjects were 13 vlogs made by students on the topic of tourism. The 13 Vlogs are assessed using the rubric developed by Dan Rooney and Elijah Punzalan. The results showed that the highest vlog value was 84 and the lowest was 74, which generally increased students' creativity. Common mistakes on average are ways of delivering or introducing introduction and introduction that are still not good, how to give conclusions or provide summaries and finally the accuracy of the grammatical structure used. There is an increase in speaking ability including vocabulary, fluency, pronunciation and intonation sections. It can be seen that there is a ratio of 2.8 points for vocabulary, 7.9 points for fluency, 10.9 points for pronunciation and 2.1 points for intonation. The findings also infer that the application of speaking through blended learning vlogging media YouTube was declared successful and improved students' speaking abilities.